Media barometer 2002 - Nordicom - Nordic Information Centre for Media and Communication Research, University of Gothenburg (University of Gothenburg, 2004)
The first Media Barometer was conducted in 1979 and since then the survey has been carried out annually. The purpose is to explore how the Swedish population is using different media during an average day.
In 2002 the respondents were asked about their usage of different media equipment such as television, text-television, radio, video recorder, CD-player/record player, and tape recorder, the day before the interview. Respondents using any of these equipments were asked about time spent using the equipment. For equipment not used the day before the respondents were asked when it was last used. Television watchers were asked about which channels they had watched. Video watchers were asked if they watched a recorded program, a rented movie or a movie they had bought. All respondents were asked if the had been reading any of the following the day before: morning paper, evening paper, weekly magazine, comics or any other magazine, or book. If so, they were asked how many and for how long period. Readers of morning and evening papers were asked if they read the printed version or the internet version. Book readers were also asked what kind of literature they were reading, and paper and magazine readers were asked about what kind of paper/magazine they read. Those respondents who answered that they did not read any paper, magazine or book the day before were asked when they last did so. The survey also includes detailed information on at what time the day before the respondent spent time reading morning paper, evening paper, listening to the radio or watching television. There is also more detailed information on which news magazines the respondent watched. The respondents also had to state what kind of advertisements they had been reading/looking to the day before. A number of questions dealt with computer usage at home and at work respectively, and the usage of Internet at home and at work. Background variables includes information on age, gender, education, occupation, and household composition.

Purpose:

Describe the trends and changes in people's use of mass media.

Mediebarometern genomfördes första gången 1979 och har sedan dess genomförts varje år. Undersökningen avser att belysa hur stor andel av den svenska befolkningen som en genomsnittlig dag tagit del av ett antal enskilda medier. Syftet är att beskriva tendenser och förändringar i människors utnyttjande av massmedier.
I Mediebarometern 2002 tillfrågades respondenterna om hur man dagen innan intervjun tagit del av radio, TV, text-TV, video, bio, ljudkassett, CD, morgontidning, kvällstidning, vecko-/månadstidning, tidskrift, bok, reklam och ny medieteknik. De personer som angav att de använt något av dessa medier tillfrågades om hur mycket tid man lagt ned på respektive massmedium. De personer som angivit att man inte läst eller tittat i en veckotidning eller tidskrift föregående dag tillfrågades om man i så fall gjort detta under någon av de föregående sex dagarna.
TV-tittarna tillfrågades vilka kanaler de tittat på och videoanvändarna fick ange om de tittat på ett inspelat program, en hyrd film eller en film man köpt. Samtliga respondenter tillfrågades om man föregående dag läst: morgontidning, kvällstidning, veckotidning, månadstidning, annan tidskrift eller bok. Om man läst något föregående dag fick man följdfrågor om hur många man läst och hur mycket tid man spenderat på läsandet. Morgon- och kvällstidningsläsare fick även besvara om man läst tidningen i tryckt version eller på Internet. Bokläsare tillfrågades vilken typ av litteratur man läst och tidskriftsläsare vilken typ av tidskrift man läst. Respondenter som svarat att man inte läst någon tidning, tidskrift eller bok dagen innan tillfrågades när man senast gjort detta.
Undersökningen innehåller även detaljerad information om vilken tid på dagen som respondenterna ägnar sig åt att läsa morgon- resp. kvällstidning, radiolyssnande och TV-tittande. Det finns även information om vilken typ av nyhetsprogram man tittat på samt vilken typ av reklam man tagit del av under föregående dag. Ett stort antal frågor behandlar användningen av persondatorer och Internet hemma och på arbetet. Bakgrundsfrågorna omfattar ålder, kön, utbildning, arbetsmarknadsgrupp, facklig huvudorganisation samt hushållets sammansättning.

Syfte:

Beskriva tendenser och förändringar i människors nyttjande av massmedier.
Mediebarometern 2002
Keywords: mass media; massmedia; mass media exposure; massmediaexponering; newspaper readership; tidnings läsekrets; periodicals readership; tidskrifts läsekrets; listening to music; musiklyssnande; book use; bokanvändning; local broadcasting; lokalsändningar; radio stations; radiostationer; satellite television; satellit-tv; television channels; tv-kanaler; cable television; kabel-tv; television news; tv-nyheter; advertising; reklam; television viewing; tv-tittande; internet; internet; internet access; internetåtkomst; electronic mail; elektronisk post; audio and video equipment; ljud- och videoutrustning; information retrieval; informationssökning; teletext; text-tv; mobile communication; mobilkommunikation; access to information and communications technology; tillgång till informations- och kommunikationsteknologi; computers; datorer; households; hushåll; radio listening; radiolyssnande; reading (activity); läsande; Media; Media; Information society; Informationssamhället; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap